Cerebral Syphilitic Gumma in Immunocompetent Man, Japan - Kodama, Tatsuya; Sato, Hidenori; Osa, Morichika; Fujikura, Yuji; Kawana, Akihiko (Emerging Infectious Diseases, 2018)
Although cerebral syphilitic gummas are generally considered to be rare manifestations of tertiary syphilis, many reports exist of early cerebral syphilitic gumma. Our finding of cerebral syphilitic gumma in an HIV-negative man within 5 months after syphilis infection suggests that this condition should be considered in syphilis patients who have neurologic symptoms.